2018
DOI: 10.3347/kjp.2018.56.4.341
|View full text |Cite
|
Sign up to set email alerts
|

Infections with Centrocestus armatus Metacercariae in Fishes from Water Systems of Major Rivers in Republic of Korea

Abstract: The infection status of Centrocestus armatus metacercariae (CaMc) was broadly surveyed in freshwater fishes from major river systems in the Republic of Korea (Korea) during 2008–2017. A total of 14,977 fishes was caught and examined by the artificial digestion method. CaMc were detected in 3,818 (97.1%) (2,114 Z. platypus: 96.1% and 1,704 Z. temminckii: 98.4%) out of 3,932 Zacco spp. examined and their density was 1,867 (2,109 in Z. platypus and 1,567 in Z. temminckii) per fish infected. The prevalences with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Fish species (No. of fish) examined were T. hakonensis (33), C. auratus (22), A. flavimanus (11), M. cephalus (11), T. brevispinis (10), A. lactipes (10), Gymnogobius castaneus (10), K. punctatus (5), Chelon haematocheilus (1).…”
Section: Fishes Examined By the Coastal Lakesmentioning
confidence: 99%
“…Fish species (No. of fish) examined were T. hakonensis (33), C. auratus (22), A. flavimanus (11), M. cephalus (11), T. brevispinis (10), A. lactipes (10), Gymnogobius castaneus (10), K. punctatus (5), Chelon haematocheilus (1).…”
Section: Fishes Examined By the Coastal Lakesmentioning
confidence: 99%
“…The chub fish species, Z. platypus , Z. koreanus and Z. temminckii , are known to be the susceptible fish hosts for C. armatus metacercariae (CaMc) in Korea [ 23 25 ]. In this study, the high endemicities with CaMc were shown in Z. platypus from Geum-gang (100% prevalence and over 3,300 CaMc intensity) in Geumsan-gun and Yugu-cheon (100% prevalence and over 7,000 CaMc intensity) in Gongju-si, Chungcheongnam-do.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the high endemicities with CaMc were shown in Z. platypus from Geum-gang (100% prevalence and over 3,300 CaMc intensity) in Geumsan-gun and Yugu-cheon (100% prevalence and over 7,000 CaMc intensity) in Gongju-si, Chungcheongnam-do. In a nation-wide survey of CaMc [ 25 ], the prevalences were very high, 93.7–100% (av. 97.1%), in chub fish species, Zacco spp., from all surveyed sites.…”
Section: Discussionmentioning
confidence: 99%
“…Fish bodies were dissected [38], gill arches were removed with the aid of a stereomicroscope (Leica, Milano, Italy) and prepared as wet mounts to be examined for the presence of encysted metacercariae [5,10,16,21,25,26,28,30,47]. Encysted metacercariae were examined under a light microscope (Leica, Milano, Italy) ( Figure 1B) to evaluate their morphology and to be identified according to published characteristics [5,[10][11][12][13][14][15][16][17]26]. Live encysted metacercariae were also recorded at 40× using a light microscope (Leica, Milano, Italy) (Supplementary Materials Video S1).…”
Section: Centrocestus Formosanus Examination and Identificationmentioning
confidence: 99%
“…Within fish-borne trematodes, Centrocestus formosanus is a small heterophyid fluke, described for the first time in Taiwan [9] and widely distributed in Asia [4,5,[10][11][12][13][14][15]. Since the 1950s, several authors have reported this species in new continents, although its occurrence could still be underestimated [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%